A review of the flying fish genus Cypselurus (Beloniformes: Exocoetidae). Part 2. Revision of the subgenus Poecilocypselurus Bruun, 1935 with descriptions of three new species and five new subspecies and reinstatement of Exocoetus apus Valenciennes and E. neglectus Bleeker - Shakhovskoy, Ilia B.; Parin, Nikolay V. (Zootaxa, 2022)
The second part of the review of flying fishes of the genus Cypselurus Swainson, 1838 covers the following: C. oligolepis (Bleeker, 1865) is a composite of six different species: C. oligolepis, C. izumii sp. nov., C. clariangulatus sp. nov., C. neglectus (Bleeker, 1865), C. nossibe sp. nov. (here placed in the subgenus Cypselurus s.str.) and Cypselurus sp.. Two of these species were found to be polytypic: C. oligolepis (with subspecies C. o. oligolepis, C. o. apus (Valenciennes, 1847), C. o. persicus subsp. nov. and C. o. georgii subsp. nov.) and C. neglectus (with subspecies C. n. neglectus and C. n. shcherbachevi subsp. nov.). Cypselurus poecilopterus (Valenciennes, 1847) is also polytypic and is divided into three subspecies: C. p. poecilopterus, C. p. arabicus subsp. nov. and C. p. crassus subsp. nov. Exocoetus apus Valenciennes (as a subspecies) and E. neglectus Bleeker are reinstated as valid. The morphology of C. starksi Abe, 1953, C. oligolepis, C. izumii, C. clariangulatus, C. neglectus and C. nossibe at different stages of ontogeny is described and maps of their geographical distribution provided. Lists of synonymy and bibliography for these species and C. poecilopterus, C. simus (Valenciennes, 1847) and C. callopterus (Günther, 1866) are compiled. A key for identification of species and subspecies of the subgenus Poecilocypselurus Bruun, 1935 and C. nossibe is provided.